2022
DOI: 10.3390/math10081312
|View full text |Cite
|
Sign up to set email alerts
|

Guided Hybrid Modified Simulated Annealing Algorithm for Solving Constrained Global Optimization Problems

Abstract: In this paper, a hybrid gradient simulated annealing algorithm is guided to solve the constrained optimization problem. In trying to solve constrained optimization problems using deterministic, stochastic optimization methods or hybridization between them, penalty function methods are the most popular approach due to their simplicity and ease of implementation. There are many approaches to handling the existence of the constraints in the constrained problem. The simulated-annealing algorithm (SA) is one of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…When a stochastic method as a global optimization algorithm is combined with a globally convergent method (deterministic method), the result is a global optimization algorithm [55,56].…”
Section: Hybridization Of the Cg Methods With Stochastic Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…When a stochastic method as a global optimization algorithm is combined with a globally convergent method (deterministic method), the result is a global optimization algorithm [55,56].…”
Section: Hybridization Of the Cg Methods With Stochastic Parametersmentioning
confidence: 99%
“…In many studies, the numerical outcomes indicated that the interbreed between a classical method and a random technique is very successful in overcoming the weakness of these methods. See [55][56][57][58][59]. Consequently, this part of the paper seeks to solve Problem (2).…”
Section: Part Ii: Global Minimization Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Many classical algorithms such as simulated annealing are computationally expensive and can take a long time to converge to a solution [27] . Additionally, these algorithms are often limited in their ability to handle large and complex molecular structures, which are common in the eld of drug discovery [28] .…”
Section: E Drawbacks Of Wet Lab and Classical Approachesmentioning
confidence: 99%
“…For engineering optimization problems, it is of great potential to pursue the optimal or the best solution to enhance diverse targets, such as production safety, efficiency, and energy consumption. However, current engineering optimization problems exhibit distinctive characteristics of multi-constraints, non-linearities, and multi-modalities, making it increasingly challenging for traditional optimization methods to handle such problems [2][3][4]. Hence, the research of effective optimization strategies for engineering optimization problems is always a hot spot.…”
Section: Introductionmentioning
confidence: 99%